Case studies on the perceived effects of inclusion on the behavior of children with mental retardation - Hsu, Yung-Han (Amanda) (Animo Repository, 2005)
This study focused on determining the perception of special and regular education teachers regarding the effects of inclusion on the behavior of children with mental retardation. It specifically sought to identify the behavior of these children when they were in a special education setting, as well as their current behavior in an inclusive setting, along with the five learning domains of cognitive, communication, socio-emotional, adaptive and physical skills. With the data obtained from the questionnaire administered to 29 teachers, from which 23 were regular education teachers and six were special education teachers, all from the three public schools in the Division of Manila City Schools as respondents, six case studies were made. 1. The study made use of descriptive-qualitative design, as it described the perceptions of the respondents. Based on these, and on the interviews made subsequently, the study also included an in depth case study of the behaviors exhibited by six children with mental retardation. The general conclusion that can be derived in that is an apparent improvement in the skills developed among CWMR who were moved from the special education classes to the regular education setting.